2014
DOI: 10.13005/bbra/1241
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice on Medical Research: The Perspective of Medical Students

Abstract: This descriptive cross sectional study was conducted to assess the level of knowledge, attitudes and practices towards research among Undergraduate Medical students. This study also focused to emphasize the need of Research Methodology training programs for undergraduate medical students. About 308 undergraduate medical students of S.R.M. Medical College, Chennai were given a structured questionnaire to evaluate their knowledge, attitudes and practices about medical research. A total of 301 returned the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
(12 reference statements)
5
5
0
Order By: Relevance
“…In the present study, lesser number of participants (36.8%) have presented poster or research paper in conference. This was in accordance with the studies done by Rani and Priya, 12 Giri et al, 11 and Pawar et al 9 The present study showed that higher number of participants have experience of writing research paper. This was not in accordance with the study conducted by Sharma et al, 13 Pawar et al, 9 and Rani and Priya.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, lesser number of participants (36.8%) have presented poster or research paper in conference. This was in accordance with the studies done by Rani and Priya, 12 Giri et al, 11 and Pawar et al 9 The present study showed that higher number of participants have experience of writing research paper. This was not in accordance with the study conducted by Sharma et al, 13 Pawar et al, 9 and Rani and Priya.…”
Section: Discussionsupporting
confidence: 93%
“…The present study concluded that maximum number of participants (67.7%) were willing to participate in workshop on research methodology. This was in accordance with studies conducted by Giri et al, 11 Rani and Priya, 12 Sharma et al, 13 and Pawar et al 9 The present studies revealed that higher number of PGs have publications in journals. Similar studies done by Giri et al 11 and Pawar et al 9 were in contradiction with our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations